Influence of the arboreal component in the productive and nutritional parameters of Brachiaria mutica grass in northeastern Peru - Valqui Valqui, Leandro (2022)
The objective of this study was to evaluate the growth (cm), yield (kg/m2), crude protein (CP %), crude fiber (CF %), ether extract (EE %), NDF (%), ADF (%), gross energy (GE kcal/kg), ELN (%), Ash (%), and in vitro digestibility (IVD %) of Brachiaria mutica grass; under three silvopastoral systems, guava (Inga edulis), poplar (Populus alba), and eucalyptus (Eucalyptus globulus labill) and a treeless system (TS) in the northeast of peru. These were analyzed under a completely randomized design (CRD) with four treatments and four repetitions, and the results were analyzed by analysis of variance (α = 0.05%) and Tukey’s means test (p ≤ 0.05). The SPS of guava showed higher growth at 30 days (59.57 cm), and the there was no difference between systems at 45 (98.43–107.14 cm), 60 (138.86–146.57 cm), and 75 days (159.81–165.67 cm); the highest yield at 30 days was for SPS with guava (0.41 kg/m2), at 45 and 60 days there was no difference (1.01–1.15 and 1.57–1.76 kg/m2), and at 75 days the highest yield was from TS (2.88 kg/m2); the nutritional composition was evaluated in two cut-off frequencies (30 and 75 days); for 30 days, the SPS with guava had a higher value for CP (16.03%), IVD (68.13%), and GE (4502 kcal/kg); the SPS with eucalyptus had a higher percentage for CF (21.08), NDF (33.17), FDA (56.42), and ash (7.74); the highest EE content was in the SPS with poplar (2.46%) and the TS presented the highest percentage of ELN (50.88); for 75 days, the SPS with guava presented a higher value for CP (13.61%), FDA (36.78), and GE (4504.33 kcal/kg), the SPS with eucalyptus had a higher percentage for CF (23.51) and ash (6.42), and the the SPS with poplar had the highest percentage of EE (2.24), ELN (59.18) FDN (62.67), and IVD (56.59).